2000
DOI: 10.1242/jcs.113.7.1277
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional transcytosis of IgG by the rat neonatal Fc receptor expressed in a rat kidney cell line: a system to study protein transport across epithelia

Abstract: The neonatal Fc receptor, FcRn, transports immunoglobulin G (IgG) across cellular barriers between mother and offspring. FcRn also protects circulating IgG from catabolism, probably during transport across the capillary endothelium. Only one cell culture model of transcytosis has been used extensively, the transport of IgA from the basolateral to the apical surface of Madin-Darby canine kidney cells by the polymeric immunoglobulin receptor (pIgR). We report that rat inner medullary collecting duct (IMCD) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(11 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…In contrast, all FcRn‐mediated transport of IgG (transcytosis in both directions and recycling from both the apical and basolateral surfaces) are inhibited by nocodazole when IgG is internalized at either acidic or basic pH (Table II), suggesting that all forms of FcRn‐mediated transport of IgG require intact microtubules. These results are consistent with those obtained for FcRn‐mediated trans cytosis in inner medullary collecting duct (IMCD) cells (McCarthy et al ., 2000). However, only basolateral to apical transcytosis of an FcγRII/FcRn chimeric protein expressed in MDCK cells was inhibited by nocodazole (Stefaner et al ., 1999), which may reflect a different mechanism for transcytosis in the apical to basolateral direction when the FcRn ectodomain is absent.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, all FcRn‐mediated transport of IgG (transcytosis in both directions and recycling from both the apical and basolateral surfaces) are inhibited by nocodazole when IgG is internalized at either acidic or basic pH (Table II), suggesting that all forms of FcRn‐mediated transport of IgG require intact microtubules. These results are consistent with those obtained for FcRn‐mediated trans cytosis in inner medullary collecting duct (IMCD) cells (McCarthy et al ., 2000). However, only basolateral to apical transcytosis of an FcγRII/FcRn chimeric protein expressed in MDCK cells was inhibited by nocodazole (Stefaner et al ., 1999), which may reflect a different mechanism for transcytosis in the apical to basolateral direction when the FcRn ectodomain is absent.…”
Section: Resultssupporting
confidence: 92%
“…We also found that the use of serum containing bovine IgG induced a similar redistribution of FcRn (data not shown). Redistribution of FcRn caused by transport of bovine IgG in serum could account in part for the predominance of basolateral surface expression over apical surface expression seen for rat FcRn expressed in IMCD cells (McCarthy et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other cells, such as epithelial cells lining mucosal interfaces, FcRn mediates IgG transcytosis, thereby participating in immune surveillance and host defense. Extensive evidence for a FcRn-dependent IgG transcytosis pathway has been gathered from in vitro studies in various polarized cell lines (e.g., refs ). This pathway was also documented in vivo in mice, and was shown to be efficient in the female genital epithelium as well as the respiratory epithelium of the lung barrier. , …”
Section: Macromolecular Transport In the Central Nervous System Acros...mentioning
confidence: 99%
“…The expression of FcRn was found at the brain microvasculature and choroid plexus epithelium [ 60 ]. It has been shown that FcRn transports IgG across cellular barriers between mother and offspring [ 61 ]. Similarly, FcRn in the BBB may facilitate the transfer of MS plasma IgG antibodies into CNS.…”
Section: Discussionmentioning
confidence: 99%